Effects of acute ocean acidification on spatially-diverse polar pelagic foodwebs: Insights from on-deck microcosms. (May 2016) - Tarling, G.A.; Peck, V.L.; Ward, P.; Ensor, N.S.; Achterberg, E.; Tynan, E.; Poulton, A.J.; Mitchell, E.; Zubkov, M.V.
Abstract: The polar oceans are experiencing some of the largest levels of ocean acidification (OA) resulting from the uptake of anthropogenic carbon dioxide (CO2 ). Our understanding of the impacts this is having on polar marine communities is mainly derived from studies of single species in laboratory conditions, while the consequences for food web interactions remain largely unknown. This study carried out experimental manipulations of natural pelagic communities at different high latitude sites in both the northern (Nordic Seas) and southern hemispheres (Scotia and Weddell Seas). The aim of this study was to identify more generic responses and achieve greater experimental reproducibility through implementing a series of short term (4 d), multilevel (3 treatment) carbonate chemistry manipulation experiments on unfiltered natural surface-ocean communities, including grazing copepods. The experiments were successfully executed at six different sites, covering a diverse range of environmental conditions and differing plankton community compositions. The study identified the interaction between copepods and dinoflagellate cell abundance to be significantly altered by elevated levels of dissolved CO2 ( p CO2 ), with dinoflagellates decreasing relative to ambient conditions across all six experiments. A similar pattern was not observed in any other major phytoplankton group. The patterns indicate that copepods show a stronger preference for dinoflagellates when in elevated p CO2 conditions, demonstrating that changes in food quality and altered grazing selectivity may be a major consequence of ocean acidification. The study also found that transparent exopolymeric particles (TEP) generally increased when p CO2 levels were elevated, but the response was dependent on the exact set of environmental conditions. Bacteria and nannoplankton showed a neutral response to elevated p CO2 and there was no significant relationship between changes in bacterial or nannoplankton abundance and that of TEP concentrations. Overall, the study illustrated that, although some similar responses exist, these contrasting high latitude surface ocean communities are likely to show different responses to the onset of elevated p CO2 .